Fabrication of a green and sensitive quantum dots based fluorescent probe for determination of sparfloxacin in biological samples and drug formulations. (5th February 2021) - Muhammad, Mian; Ara, Behisht; Ali, Faiz; Ullah, Ikram
Abstract: A simple and fast spectrofluorimetric method for determination of sparfloxacin (SPAR) based on fluorescence quenching of colloidal water soluble TGA caped, Mn doped ZnS quantum dots (QDs) has been described. The QDs having characteristic fluorescence spectra with maximum emission at 632 nm (Excitation at 315 nm) were characterized using Energy Dispersive x-ray and x-ray Diffraction techniques. The effect of various parameters such as concentration of QDs, time, pH, common excipients and metal ions on the quenching phenomenon was investigated. Fluorescence quenching was found to be maximum with 10 μ g ml −1 of QDs at pH 7 with fluorescence intensity remaining constant upto 60 min. The Stern-Volmer calibration plot of F 0 /F as a function of sparfloxacin concentration was found to be linear in the range of 0.2–2.2 μ g ml −1 with r 2 = 0.995. Under optimal experimental conditions the method was found to be interference free. The percent relative standard deviation of the proposed method calculated against method blank was found to be 1.67%. The limit of detection and the limit of quantitation for SPAR (n = 3 and 10 respectively) were calculated to be 0.07 and 0.21 μ g ml −1 respectively. Average percent recoveries (±SD) obtained were found to be 89.16 ± 0.03 to 94.44 ± 0.15 μ g ml −1 for serum and 85.00 ± 0.10 to 97.77 ± 0.37 μ g ml −1 for urine samples. In case of commercial formulations sparaxcin and spar, the maximum % recovery was found to 89.33 ± 0.54% while in case of Quspar the % recovery obtained was less than 71.83 ± 0.14%. The proposed method was statistically compared with reported chromatographic method and no significant difference was observed.